PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS APLIKASI ANDROID PADA MATERI SISTEM IMUNITAS - Julsa Arofian; Agus Sujarwanta; Triana Asih (BIOEDUKASI (Jurnal Pendidikan Biologi), 2022)
This research is a research and development research and development (R&D) that aims to develop interactive learning media in the immune system material based on android applications. The learning media developed in this study is a form of learning media innovation that is able to follow the modern era by utilizing the Android system through the Playstore feature. The product trial developed was carried out on students of class XI Science SMA N 1 Bandar Sribhawono, before the product trial was carried out a validation stage was carried out by a team of experts from the Muhammadiyah Metro University lecturer. Based on the data analysis, it was obtained that the overall percentage value of the expert team was 90.8%, so the media developed was included in the "very feasible" category for use. The product trial phase for students obtained results for the good category of 64.8% and the very good category of 27.4% so that the results obtained for the feasibility of the product were 92.2%. The results of these calculations can conclude that this android-based application is "very feasible" to be used in the learning process. Kata Kunci: android, Media Pembelajaran Interaktif Analisis Kebutuhan, Pengembangan